Shooting up illicit drugs with God and the State: the legal–spatial constitution of Sydney's Medically Supervised Injecting Centre as a sanctuary. (21st December 2015) - Prior, Jason; Crofts, Penny
Abstract: In 1999, the Uniting Church opened a Medically Supervised Injecting Centre (MSIC) at the Wayside Chapel in the inner Sydney suburb of Kings Cross. The Uniting Church justified this overt act of civil disobedience against the State's prohibitionist model of drug usage by invoking the ancient right of sanctuary. This invocation sought to produce a specific sort of spatialisation wherein the meaning of the line constituting sanctuary effects a protected 'inside' governed by God's word – civitas dei – 'outside' the jurisdiction of state power in civitas terrena . Sanctuary claims a territory exempt from other jurisdictions. The modern assertion of sanctuary enacts in physical space the relationship between state and religious authorities and the integration and intersections of civitas terrena and civitas dei . This article draws upon conceptions of sanctuary at the intersection of the Catholic Christianity tradition and the State since medieval times to analyse the contemporary space of sanctuary in the MSIC, exploring the shifting and ambiguous boundaries in material, legislative, and symbolic spaces. We argue that even though the MSIC has now been incorporated into civitas terrena, it remains and enacts a space of sanctuary.